2004
DOI: 10.1038/sj.emboj.7600217
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent degradation of c-Myc is mediated by the F-box protein Fbw7

Abstract: The F-box protein Skp2 mediates c-Myc ubiquitylation by binding to the MB2 domain. However, the turnover of cMyc is largely dependent on phosphorylation of threonine-58 and serine-62 in MB1, residues that are often mutated in cancer. We now show that the F-box protein Fbw7 interacts with and thereby destabilizes c-Myc in a manner dependent on phosphorylation of MB1. Whereas wild-type Fbw7 promoted c-Myc turnover in cells, an Fbw7 mutant lacking the F-box domain delayed it. Furthermore, depletion of Fbw7 by RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
712
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(738 citation statements)
references
References 50 publications
(103 reference statements)
23
712
2
1
Order By: Relevance
“…A fraction of active GSK-3 trafficks to the nucleus where it colocalizes with c-Myc, consistent with its role in phosphorylating c-Myc and regulating its stability (Gregory et al, 2003). Once phosphorylated at T58 by GSK3, c-Myc is recognized by Fbw7, a component of the SCF(Fbw7) ubiquitin ligase that is responsible for directing proteasome-mediated degradation (Welcker et al, 2004a, b;Yada et al, 2004). Upstream of c-Myc there remains a major gap in knowledge about the mechanisms that support accumulation of active GSK-3 in the nucleus.…”
Section: Introductionmentioning
confidence: 82%
“…A fraction of active GSK-3 trafficks to the nucleus where it colocalizes with c-Myc, consistent with its role in phosphorylating c-Myc and regulating its stability (Gregory et al, 2003). Once phosphorylated at T58 by GSK3, c-Myc is recognized by Fbw7, a component of the SCF(Fbw7) ubiquitin ligase that is responsible for directing proteasome-mediated degradation (Welcker et al, 2004a, b;Yada et al, 2004). Upstream of c-Myc there remains a major gap in knowledge about the mechanisms that support accumulation of active GSK-3 in the nucleus.…”
Section: Introductionmentioning
confidence: 82%
“…This finding explains the frequently elevated expression of cyclin E in breast tumors lacking active Fbw7 (Ekholm-Reed et al, 2004). Other substrates include the oncoproteins c-Myc (Moberg et al, 2004;Welcker et al, 2004;Yada et al, 2004), c-Jun (Nateri et al, 2004;Wei et al, 2005) and Notch (Gupta-Rossi et al, 2001;Oberg et al, 2001;Wu et al, 2001), all of which act to increase cell volume, proliferation and de-differentiation. In addition, Aurora A kinase, an important regulator of mitosis that is frequently overexpressed in human cancer tissues, also serves as a substrate of Fbw7 (Mao et al, 2004;Fujii et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…20 Several E3 ligases, including FBW7, SKP2, TRUSS, HectH9, β-Trcp1 and Hsc70-interacting protein (CHIP), have been identified as responsible for c-Myc degradation. 19,[22][23][24][25][26][27][28] However, it is still unclear whether c-Myc stability is regulated by ubiquitin-independent pathways. In the present study, we demonstrated that proteasome activator REGγ is a novel negative regulator of c-Myc and provided evidence that this regulation is evolutionarily conserved.…”
mentioning
confidence: 99%